KUALITAS TIDUR PADA DEWASA AWAL DITINJAU DARI REGULASI DIRI, KECENDERUNGAN KECANDUAN SMARTPHONE, DAN PENUNDAAN WAKTU TIDUR - Konradus, Natalia; Julianti, Annisa; Handayani, Nita Sri; Fauziah, Alia R.; Maryani, Tri (Universitas Gunadarma, 2024)
Sleep is essential for a person's life. Quality sleep will affect a person's condition in living their days. Many things can disrupt a person's sleep quality, including excessive smartphone use, bedtime procrastination, and low self-regulation. This study aimed to empirically examine the influence of sleep delay, smartphone addiction tendencies, and self-regulation on sleep quality in early adult smartphone users. The sampling technique in this research is non-probability sampling. The sample in this study was 149 early adult smartphone users with an age range of 18-40 years. Data collection in this study used a sleep delay scale, smartphone addiction scale, self-regulation scale, and sleep quality scale. Based on the results of multiple regression analysis, it is known that the significance level is 0.000 (p<0.01), with an RSquare value of 0.461 (46.1%). This shows that the influence of self-regulation, smartphone addiction tendencies, and bedtime procrastination on the sleep quality of early adult smartphone users is very significant. Apart from that, it appears that self-regulation, smartphone addiction tendencies, and bedtime procrastination affect the sleep quality of early adult smartphone users by 46.1% while other factors outside this research influence the remaining 53.9%.